Bride of the death god. 1 - Ichiiro, Hako (Square Enix Manga & Books, 2025)
When a death god appears before Aibi, a girl suffering from an incurable disease, he expects her to cry and beg for her life like all the other humans he's brought to the afterlife. But she simply smiles and thanks him for coming to her. After a lifetime of suffering-and with only seven days left to live-will Aibi finally find happiness in the arms of a reaper? This is the story of a death god who was welcomed for the first time and a young woman no longer welcome in her own world-a tale of love that even death cannot part.